Power electronics semiconductor switches - Ramshaw, Raymond (Chapman & Hall, 1993)
Power Electronic Semiconductor Switches is the successor to Professor Ramshaw's widely-used Power Electronics. The text has been completely re-written and expanded to focus on semiconductor switches, and to take into account advances in the field since the publication of Power Electronics and changes in electrical and electronic engineering syllabuses.